The Concept of Punishment In Education: A Sociological Analysis of Disciplinary Practices and their Implications for Students' Social Behavior - Hardianty, Sri (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
Implementation of punishment in education is a common practice as a learning tool in instilling discipline. This study aims to explore the concept of punishment in education, types of punishment, punishment practices and their impact on students' mental and emotional development. The research method used is a qualitative approach based on literature studies by analyzing information from relevant literature. The sample was selected using a purposive sampling technique with a homogeneous sampling type where researchers choose reference sources that have similar characteristics to explore the research phenomenon. The data analysis used is thematic analysis. The results of the study indicate that punishment in education should function as an educational learning tool, not just a restraint. The types of punishment in education are physical, verbal, social, and academic punishment. The approach to punishment needs to consider religious, cultural, and modern educational values. Currently, the practice of punishment is shifting towards an educational approach by reducing physical punishment in order to maintain students' mental health. The impact of the implementation of punishment is highly dependent on the type and method of implementation. Harsh punishment can have negative effects on students, while a corrective and reflective punishment approach can increase responsibility and create a learning environment conducive to student character development. The recommendation resulting from this study is to suggest that educators switch to more humanistic, educative and restorative punishment methods, in order to increase the effectiveness of student discipline development.